2015
DOI: 10.4238/2015.march.31.17
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on the association between ERCC1 rs3212986 and ERCC2 rs13181 polymorphisms and glioma risk

Abstract: ABSTRACT. Several studies have examined the association between excision repair cross-complementation group 1 (ERCC1) C8092A and ERCC2 Lys751Gln polymorphisms and glioma risk, but the results have been inconclusive. We conducted a meta-analysis of 12 studies to determine the association between ERCC1 rs3212986 and ERCC2 rs13181 genes and glioma susceptibility. We searched for relevant studies in both Chinese and English in PubMed, Web of Science, Cochrane Library, and EMBASE through January 1, 2014, and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…In our current review and analysis, the GG and TG genotypes showed no relationship with the development of glial tumors, corroborating the studies by Xin et al [31] and Zhou et al [32] (Fig. 2 and Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our current review and analysis, the GG and TG genotypes showed no relationship with the development of glial tumors, corroborating the studies by Xin et al [31] and Zhou et al [32] (Fig. 2 and Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Xu et al [25] found an increased risk only in Asians with CT + TT genotype and in both Asians and Caucasians with TT genotype. There are currently also systematic reviews in the literature that include meta-analysis and report a relationship between the XRCC1 rs1799782 polymorphism and its genotypes with the development of glial tumors [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the rs13181 SNP of the ERCC2 gene was found in all samples. However, no statistically signi cant differences in the expression of the GG, GT, and TT genotypes between high-and low-grade gliomas were observed, consistent with the ndings of Qian et al [24] and Zhou et al [25], and divergent from those of Huang et al [26], Cui et al [27] and Jia et al [28], who showed an increased risk, particularly in relation to the GT genotype in the Asian population.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies have shown an association between the rs13181 variant of the ERCC2 gene and the risk of developing gliomas [21,22,23]. However, most of these studies were conducted only in Asian populations and showed contradictory results regarding the in uence of genotypes of this variant in the development of glial tumors [24][25][26][27][28]. In the present study, the rs13181 SNP of the ERCC2 gene was found in all samples.…”
Section: Discussionmentioning
confidence: 43%
“…To date, several meta-analyses reported the association between ERCC1 or ERCC2 polymorphisms and glioma risk, whereas these studies only focused on the 2 polymorphisms (rs3212986 in ERCC1 gene and rs13181 in ERCC2 gene). [1621] Moreover, some recent studies involving glioma risk and ERCC polymorphisms were not included. [2225] Thus, we conducted a comprehensive meta-analysis to investigate whether 6 polymorphisms in ERCC1 (rs3212986 and rs11615), ERCC2 (rs13181, rs1799793 and rs238406), and ERCC5 (rs17655) genes are risk factors to the glioma susceptibility.…”
Section: Introductionmentioning
confidence: 99%